Factors Influencing Pediatric Weight Estimation - Srimahadthai, Sirote (Journal of Health Science of Thailand, 2020)
The objective of this study was to determine the factors that influence pediatric weight estimation. It was conducted as a cross-sectional analytic study at the pediatric outpatient department, Ratchaburi hospital. Written informed consent was obtained from all participants. Patient characteristics were presented in descriptive analysis such as percentage, mean, and standard deviation. Age, height, head circumference, midarm circumference for prediction with weight were analyzed by multiple regression analysis. The results revealed that 290 patients were enrolled. 147 patients were male (50.7%). The mean age was 4.6 years. Weight range was 8 to 29 kg. The mean weight was 17.34 kg., and the mean height was 105.84 centimetre. Midarm circumference range was 12 to 26 cm and mean of midarm circumference was 17.4 centimetre. Correlation of weight with age, height, midarm circumference and head circumference was significant. Weight (Kg) = 0.436x (midarm circumference)+0.857x(age)+0.111x(height)-5.913. In conclusions, head circumference, midarm circumference, height and age were found to be related with body weight of pediatrics. All of them could be used to predict pediatric weight.